Association between a dietary quality index based on the food standard agency nutrient profiling system and cardiovascular disease risk among French adults. (1st May 2017) - Adriouch, Solia; Julia, Chantal; Kesse-Guyot, Emmanuelle; Ducrot, Pauline; Péneau, Sandrine; Méjean, Caroline; Assmann, Karen E.; Deschasaux, Mélanie; Hercberg, Serge; Touvier, Mathilde; Fezeu, Léopold K
Abstract: Background: In France, the implementation of a front-of-pack (FOP) nutrition label–the 5-Colour Nutrition Label (5-CNL) is currently under consideration as a strategic tool to allow consumers making healthier food choices. This FOP label is based on the British Food Standards Agency Nutrient Profiling System (FSA-NPS), reflecting the overall nutritional quality of foods. At the individual level, an energy-weighted mean of all FSA-NPS scores of foods usually consumed has been elaborated (FSA-NPS DI). Our objective was to investigate the prospective association between the FSA-NPS DI and cardiovascular disease (CVD) risk. Methods: 75, 801 participants to the NutriNet-Santé cohort, who completed at least three 24 h dietary records during the first 2 y of the follow-up, were followed between 2009 and 2016. Multivariable Cox proportional hazards models were used to characterize the associations between FSA-NPS DI and the incidence of CVDs. Results: 509 major cardiovascular events were diagnosed (262 coronary heart diseases and 247 strokes). A higher FSA-NPS DI, characterizing lower dietary quality, was associated with increased CVD risk (HRfor a 1-point increment = 1.08 (1.03–1.13); HRQ4vs.Q1 = 1.40 (1.06–1.84), Ptrend Q4-Q1 = 0.01). This association tended to be stronger in overweight subjects (HRfor a 1-point increment = 1.12 (1.04–1.19); Pinteraction = 0.003). Conclusions: These results suggest that lower dietary quality, as reflected by a higher FSA-NPS DI, may be associated with a significant increase in cardiovascular risk, especially in at-risk individuals (overweight population). They support the public health relevance of developing a front-of-pack nutrition label based on this score.